Frequência de alterações clínicas da deglutição e fatores associados em idosos institucionalizados - Xavier, Jéssica Soares (2020)
Introduction: Older adults are more susceptible to swallowing disorders and associated complications, becoming even more vulnerable when living in nursing homes (ILPI). Purpose: To verify the frequency of clinical swallowing disorders and the associated factors in older adults living in nursing homes. Method: This is an observational, transversal, descriptive and quantitative study. The sample was composed by 73 older adults, mean age of 80 (SD±7.49) years, being 60 (82.2%) women, residents in five nonprofit ILPI of the city of Natal/RN. Sociodemographic, economic, and general health data were collected and the following instruments were applied: Rastreio de Disfagia em Idosos (RaDI), Volume- Viscosity Swallow Test (VVS-T) e Functional Oral Intake Scale (FOIS). The frequency of clinical swallowing disorders was determined by the result of MECV-V. To verify the factors associated with the outcome, Pearson's chi-square or Fisher's exact tests were initially applied. Variables with a p-value less than 0.20 were included in the multiple logistic regression analysis model. The significance level was 5%. Results: Among the 73 older adults assessed, 46 (63%) presented clinical swallowing disorders. The multiple logistic regression model revealed that the chance of the institutionalized older adult to present clinical swallowing disorders increases 8% with each 1 year increase in age; the decrease in food intake increases approximately 4 times the chance of a negative result in MECV-V; institutionalized older adults with a level below 7 in the FOIS scale present almost 11 times more chances of having clinical swallowing disorders according to MECV-V. Conclusion: The frequency of clinical swallowing disorders in older adults is high and is associated with age, decreased food intake, and functionality of oral intake.